2011
DOI: 10.1111/j.1582-4934.2010.01086.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac injection of matrigel induces stem cell recruitment and improves cardiac functions in a rat myocardial infarction model

Abstract: Matrigel promotes angiogenesis in the myocardium from ischemic injury and prevents remodelling of the left ventricle. We assessed the therapeutic efficacy of intracardiac matrigel injection and matrigel-mediated stem cell homing in a rat myocardial infarction (MI) model. Following MI, matrigel (250 μl) or phosphate-buffered solution (PBS) was delivered by intracardiac injection. Compared to the MI control group (MI-PBS), matrigel significantly improved left ventricular function (n= 11, P < 0.05) assessed by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 56 publications
1
41
0
Order By: Relevance
“…14 Various natural polymers such as fibrin, 15 collagen, 16,17 Matrigel, 18 chitosan, 19,20 keratin, 21 and hyaluronic acid 22,23 have been investigated as injectable hydrogels to treat MI. They have excellent biocompatibility and can promote cell migration, proliferation, and/or differentiation, leading to ultimate heart regeneration/repair.…”
mentioning
confidence: 99%
“…14 Various natural polymers such as fibrin, 15 collagen, 16,17 Matrigel, 18 chitosan, 19,20 keratin, 21 and hyaluronic acid 22,23 have been investigated as injectable hydrogels to treat MI. They have excellent biocompatibility and can promote cell migration, proliferation, and/or differentiation, leading to ultimate heart regeneration/repair.…”
mentioning
confidence: 99%
“…These parameters have been widely used for assessment of cardiac function previously (Rungwerth et al, 2004;Ou et al, 2011;Choudhery et al, 2012;Leblanc et al, 2013;Mao et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is also the possibility that a foreign-body reaction to Matrigel occurs in vivo. However, Matrigel has been used for tissue engineering in vivo without problems related with foreign-body reaction in several previous studies [1,4,8,17,21]. Besides, some reports have demonstrated that Matrigel promoted stem cell survival in vivo [1,2,4].…”
Section: Discussionmentioning
confidence: 99%